Modified Finch And Skea Stellar Model In Higher Dimensions - A. Jangid; S. Das; B. S. Ratanpal; K. K. Venkataratnam
Within the framework of higher dimensions, we enhance the model of Pandya and Thomas and assume that the system is anisotropic in the Finch and Skea ansatz. Our model explores various physical parameters in higher dimensions, including mass, energy density, radial and transverse pressures, and the anisotropy factor. We have used graphical technique to analyse the energy conditions, equilibrium conditions, and stability across different dimensions. Furthermore, the mass of a particular compact object have shown to increase with radial parameter as space-time dimensions increase. Additionally, by generating a mass-radius (M-R) plot, we demonstrate the influence of dimensional factor on the maximum mass and radius allowed by our toy model.
Keywords: Stars